Tindakan Main Hakim Sendiri (Eigenrichting) Terhadap Pelaku Khalwat Sebagai Dalih Kebiasaan Masyarakat Di Aceh - Syarifah Rahmatillah; Amrullah Bustamam (Institut Agama Islam Negeri Padangsidimpuan, 2021)
This study discusses the act of vigilantism (eigenrichting) carried out by a group of people in the community against men and women who are suspected of committing acts of khalwat in Aceh, such as persecution, beating, confinement, or other acts of hurt or distress. This research is a descriptive qualitative research, which studies in depth and holistically with the type of field research and uses a sociological juridical approach. Data obtained through observation and interviews conducted independently and controlled. While the data were analyzed using four components of interactive analysis, namely data collection, data reduction, data presentation, and drawing conclusions/verification. The results of the study show that, firstly, vigilantism is still practiced by the community against the perpetrators of khalwat, such as bathing with sewage water, hitting, parading around the village of the perpetrators of seclusion. Second, the Government through the Department of Islamic Law and Wilayatul Hisbah in Langsa City, Banda Aceh and Aceh Besar District has made various efforts to minimize vigilante treatment by socializing the provisions of the Jinayah Qanun related to procedures for resolving cases of seclusion